Switching dynamics in non-volatile polymer memories - Verbakel, F. (2014)
The time dependence of resistive switching in metal-metal oxide-organic semiconductormetal diodes is investigated. The switching dynamics is controlled by two intrinsic time dependences. A single switching event occurs in a time scale of 400 nanoseconds, but the maximum repetitive switching between ON- and OFF-states is limited by a ‘‘dead time” of a few milliseconds. The dead time is the waiting time after programming in which a next switch is inhibited. Therefore, fast repetitive pulsing prevents the observation of non-volatile switching and limits the maximum clock rate at which these memories can be used. Understanding the origin of this dead time is crucial to future memory applications. Furthermore,the occurrence of a dead time is possibly the origin of the huge variation in the reported switching times.